Ibdaʼ ṣaghīran fakkir kabīran : unsub ṭuruq al-tadrīs fī faṣl yutafahamu waẓāʼif al-makhkh - Gregory, Gayle; Kaufeldt, Martha, 1954-; Gregory, Gayle (Majmūʻat al-Nīl al-ʻArabīyah, 2015)
Differentiation is the core of the art and science of teaching. However even masters of this art may not be effective in the classroom if they don't have a basic understanding of how the human brain griows, develops, and learns: To successfully implement differentiation strategies, educators must design and orchestrate a brain compatible environment. Think Big, Start Small pares down the vast field of enuroscience and provides educators with the brain basic needed to create a classroom that enhances learning.